Territory, city and architecture - El-Daccache, Maroun (2008)
It seems like all the architectural debates are finished as nobody cares for the “old” problems like people or lodgings. Architecture today means publicity and its beauty follows is the subject to the same conditions. The risk is that architecture has become an object design.